Leader based group routing in disconnected mobile ad hoc networks with group mobility - Xie, Ling Fu (2013)
When there is disconnection in mobile ad hoc network under group mobility, it falls into the delay-tolerant network (DTN). However, most existing research in DTN targets entity mobility. In this paper, we consider the routing strategy for DTN with group mobility, and propose the leader based group routing (LBGR) by making full use of group structure in group mobility. Three major mechanisms closely related to the group mobility are proposed in LBGR. First, we treat each group as one individual unit during routing execution to substantially reduce the routing overhead and the resource requirement. Second, we consider the resource allocation in each group and propose the leader-dominating routing in LBGR to reduce the impact of the group dynamics on network performance. Third, to make better use of the rare contact opportunities in DTN, we propose the group based packet exchange, in which the contact of any two nodes from two groups will trigger the packet exchange between the two groups. By extensive simulation we show that LBGR outperforms two traditional routing protocols, epidemic routing and DSR, in various network conditions. Especially, we will find that the impact of the group dynamics on LBGR is very limited.